Тенденції зміни попиту на перевезення вантажів у Львівській області - Фурман, Олег; Ляхович, Юстина; Рогальський, Роман (Посвіт, 2019)
In this paper, are highlighted the results of the analysis of data from the Main Directorate of Statistics of Lviv region. On the basis of this data, was established dynamics of change amount transportation of cargo and passengers in the Lvivr egion for 2015-2018.
Changes trends of cargo transportation in Lviv region
Keywords: 656.13